Mitigating negative emotions through virtual reality and embodiment - Sansoni, Maria; Scarzello, Giovanni; Serino, Silvia; Groff, Elena; Riva, Giuseppe (Frontiers in Human Neuroscience, 2022)
Oncological treatments are responsible for many of the physical changes (aesthetic and functional) associated with cancer. Because of this, cancer patients are at high risk of developing mental health problems. The aim of this study is to propose an innovative VR training that uses a somatic technique (i.e., embodiment) to create a bridge with the bodily dimension of cancer. After undergoing psycho-educational procedure, a combination of exposure, out-of-body-experience and body swapping will gradually train the patient to cope with cancer-related difficulties, increasing stress tolerance and patient’s empowerment. The most engaging step of this advanced form of Stress Inoculation Training is the Body Swapping experience, that will guide the patient in embodying a resilient cancer patient who is facing similar difficulties.Through VR ability to simulate the human brain functioning, and the potential of embodiment to hook to the somatic dimension of illness, we expect that once the concepts endured through the patient’s experience of resilience are triggered, the patient will be more prone to implement functional coping strategies in real life, reaching empowerment and adjusting to the post-treatment difficulties. When the scenarios are built and the training tested, our intervention could be used to support patients with different oncological diseases and who are treated in different cancer hospitals. Future research should focus on using our paradigm for other clinical populations as well as with cancer patients but supporting them in coping with different distressing situations.